Deterring white-collar crime: insights from Australia's insider trading penalties regime. Issue 2 (3rd July 2017) - Hanrahan, Pamela F
Abstract : In Australia, insider trading by individuals or corporations can attract either criminal or civil penalties. This article considers the potential deterrent effect of the different types of penalties for illegal insider trading and concludes that while criminal prosecution remains the preferred enforcement option in relation to wrongdoing by individuals motivated by personal gain, civil penalty proceedings may be a more effective deterrent of unlawful conduct by individual wrongdoers motivated by corporate success, or by corporations. If so, this may have implications for penalties design in relation to other forms of white-collar crime, at least where the harm caused is not to an individual victim.